(untitled) (Annals of Medical Research, 2021)
Aim: Acute graft-versus-host disease (GVHD) is an complication after allogeneic hematopoietic stem cell transplantation (allo-HSCT), manifesting with an erythematous maculopapular rash followed by liver disease and dysfunctions of the gastrointestinal tract. This study aimed to retrospectively investigate the demographic and clinical characteristics of pediatric patients diagnosed with acute GVHD after undergoing allo-HSCT due to various hematological diseases.Material and Methods: The study included 33 pediatric patients that underwent their first allogeneic bone marrow transplantation in the Pediatric Bone Marrow Transplant Unit between 2015 and 2018 and were consecutively diagnosed with acute GVHD in consultation with the department of dermatology. The demographic characteristics, clinical findings, donor characteristics, treatments, and survival status of each patient were recorded.Results: Between 2015 and 2018, bone marrow transplantation was performed in 150 pediatric patients, of whom 33 (22%) developed acute GVHD. Of the 33 pediatric patients, 19 (57.6%) were boys and 14 (42.4%) were girls. At the time of transplantation, the mean age of the patients was 8.5 years, and the median age was 7 years. Twenty patients (60.6%) had only skin GVHD while 13 (39.4%) had skin and gastrointestinal and/or hepatic GVHD. It was found that the rashes had appeared on average 27.4 days after allo-HSCT. Palmoplantar involvement was detected in 13 patients (39.4%), painful erosion in the oral mucosa in 11 (33%), and conjunctivitis in seven (21.2%). The factors of being a male patient, being a female donor, transplantation from unrelated donors, liver involvement, and palmoplantar involvement were found to create risk of mortality, but not significantly (respectively p=0,753;p=0,145,0,66). Five patients (15%) progressed from acute to chronic GVHD. In patients that progressed from acute to chronic had, the mean donor age was higher, the mean time from transplantation to rash was longer, and oral involvement was higher, but not significantly (respectively; p=0,596;p=0,980;p=0,193.Conclusion: In acute GVHD, the skin is the first and most involved organ; therefore, dermatologists play an important role in its diagnosis. This study is important for determining the factors affecting the decrease in progression to chronic GVHD and prolonging survival.